Negotiating outside the law : why Camp David failed - Helmick, Raymond G. (Pluto Press, 2004)
"In the summer of 2000, President Clinton, Ehud Barak and Yasser Arafat came together to negotiate peace between Israel and Palestine. Jesuit priest and longtime peace active Raymond G. Helmick was one of the few people who remained in contact with what went on. He maintained communication with all parties - including President Clinton - throughout." "This book is his starting account of the arguments, the relationships and the strategies that played our over the summer of 2000. Based on personal correspondence and position papers with all three leaders, and a long personal association with Yasser Arafat and a whole series of Israeli Prime Ministers dating back to 1985, this book offers a unique account of the real reasons behind the failure of Camp David."--Jacket